2013
DOI: 10.1371/journal.pone.0060968
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prenatal Molecular Karyotyping from Maternal Plasma

Abstract: Fetal DNA is present in the plasma of pregnant women. Massively parallel sequencing of maternal plasma DNA has been used to detect fetal trisomies 21, 18, 13 and selected sex chromosomal aneuploidies noninvasively. Case reports describing the detection of fetal microdeletions from maternal plasma using massively parallel sequencing have been reported. However, these previous reports were either polymorphism-dependent or used statistical analyses which were confined to one or a small number of selected parts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 26 publications
0
60
0
2
Order By: Relevance
“…The actual diagnostic impact of such algorithms would require future validation using large sample cohorts. At present, we would predict that the AND algorithm and its associated enhancement in specificity would be of value if one wishes to expand the clinical spectrum of noninvasive prenatal testing, e.g., for chromosomal microdeletions or even obtaining a genomewide molecular karyotype (28)(29)(30)(31). It is also possible that an even higher level of diagnostic specificity could be achieved by combining size, count, and DNA methylation information (32).…”
Section: Discussionmentioning
confidence: 99%
“…The actual diagnostic impact of such algorithms would require future validation using large sample cohorts. At present, we would predict that the AND algorithm and its associated enhancement in specificity would be of value if one wishes to expand the clinical spectrum of noninvasive prenatal testing, e.g., for chromosomal microdeletions or even obtaining a genomewide molecular karyotype (28)(29)(30)(31). It is also possible that an even higher level of diagnostic specificity could be achieved by combining size, count, and DNA methylation information (32).…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the z-scores genome wide in 5 Mb intervals, which provides a genome-wide visualization of all potential fetal abnormalities. Similar, although slightly different in approach, genome-wide scanning of binned z-scores has been applied before, to demonstrate the feasibility to noninvasively detect fetal subchromosomal imbalances by deep sequencing, 42,43 as well as by 'shallow-depth' sequencing. 44 Whereas those studies have focused on the ability to detect noninvasively ever smaller fetal copy number variants with the aim to reduce the need for invasive sampling and chromosomal microarray analysis, we have focused on using this additional information to improve the quality of the aneuploidy detection.…”
Section: Discussionmentioning
confidence: 99%
“…A number of case reports, as well as retrospective and prospective validation studies of novel algorithms, have recently been reported on the ability to detect segmental imbalances and even submicroscopic CNVs. 5,13,20,29,[43][44][45][46][47][48] Lau et al 29,47 reported on the use of the FCAPS pipeline detecting a fetal duplication of 18p, which is 14 Mb in size. Here, we show the detection of a segmental trisomy 18, which is 29 Mb in size, demonstrating the power of this genome-wide profiling approach.…”
Section: Discussionmentioning
confidence: 99%
“…It would be advantageous if one could identify the tissue of origin of the copy number aberrations. For the noninvasive prenatal detection of subchromosomal copy number aberrations (33), it would be useful to identify if the plasma aberrations originated from (i) the placenta alone, (ii) the mother alone, or (iii) both the placenta and the mother. As another example, if the detection of plasma copy number aberrations is eventually used as a cancer screening tool (10,11,32), it would be clinically very informative to be able to identify the tissue of origin of the cancer for subsequent diagnostic or therapeutic procedures.…”
Section: Plasma Dna Methylation Deconvolution In Posttransplantationmentioning
confidence: 99%